PRINCIPLES OF TEACHING PEDAGOGICAL SCIENCE IN HIGHER EDUCATIONAL INSTITUTIONS - Erkaboeva Nigora Shermatova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the principles of teaching pedagogy in Higher Educational Institutions. Proposals were also developed based on the conclusions drawn.